2013
DOI: 10.1590/1678-775720130066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silica coating and silane surface treatment on the bond strength of soft denture liner to denture base material

Abstract: O bjective: This study investigated the effects of different surface treatments on the tensile bond strength of an autopolymerizing silicone denture liner to a denture base material after thermocycling. Material and Methods: Fifty rectangular heat-polymerized acrylic resin (QC-20) specimens consisting of a set of 2 acrylic blocks were used in the tensile test. Specimens were divided into 5 test groups (n=10) according to the bonding surface treatment as follows: Group A, adhesive treatment (Ufi Gel P adhesive)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 18 publications
2
37
0
Order By: Relevance
“…[11][12][13][14][15] Gundogdu et al 14 and Akin et al 11 reported that roughening the acrylic resin with airborne particle abrasion with 50-µm alumina particles resulted in lower bond strength compared to control specimens. Similar findings were reported by Atsü and Keskın, 16 who found that airborne abrasion with 50-µm alumina and 30-µm silica-coated alumina particles did not improve the bond strength of resilient lining material to denture base resin. It has been proposed that the weakening effect of airborne abrasion on the bond strength might be due to stresses that are produced at the acrylic resin-resilient liner interface or to insufficient size of irregularities created by airborne abrasion to allow penetration of material into them.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[11][12][13][14][15] Gundogdu et al 14 and Akin et al 11 reported that roughening the acrylic resin with airborne particle abrasion with 50-µm alumina particles resulted in lower bond strength compared to control specimens. Similar findings were reported by Atsü and Keskın, 16 who found that airborne abrasion with 50-µm alumina and 30-µm silica-coated alumina particles did not improve the bond strength of resilient lining material to denture base resin. It has been proposed that the weakening effect of airborne abrasion on the bond strength might be due to stresses that are produced at the acrylic resin-resilient liner interface or to insufficient size of irregularities created by airborne abrasion to allow penetration of material into them.…”
Section: Discussionsupporting
confidence: 90%
“…To solve this perplexing problem, investigators have focused on methods to alter the denture base resin surface. These methods include airborne particle abrasion, [11][12][13][14][15] tribochemical coating, 16 chemical etching, 14 and laser treatment. 14,15,17,18 A study showed that roughening the acrylic surface results in almost twice the adhesive bond strength of resilient lining materials in comparison to smooth surfaces.…”
Section: Jcdpmentioning
confidence: 99%
“…However, some problems are associated with the use of resilient denture liners, including low tear strength, porosity, colonization by Candida albicans, and frequent bond failure between the liner and denture base during clinical use [2]. Debonding between the liner and denture base may create an environment for potential bacterial growth and accelerated breakdown of the soft liner [6,7]. Therefore, the lack of durable bond to the denture is major problem for the longevity of such prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…Resilient relining materials are associated with resin and act to absorb and redistribute forces on the prosthesis . In addition, they are used to improve the adaptation of the prosthesis with the objectives of preserving support structures, giving comfort to the patient, and alleviating conditions of local chronic pain …”
mentioning
confidence: 99%
“…Silicone‐based reliners maintain their properties for a longer period of time compared to resin‐based materials, but they do not possess adequate chemical adhesion to acrylic resin, thus requiring additional resources to optimize the bond . Among the resources cited in the published literature, the use of adhesive primers before the application of the relining material is highlighted.…”
mentioning
confidence: 99%